PERGESERAN NILAI-NILAI BUDAYA DAN TRADISI DALAM UPACARA TINGKEBAN PADA MASYARAKAT SUKU JAWA DI NAGARI PADANG CANDUH, KECAMATAN KINALI, KABUPATEN PASAMAN BARAT - Valentina Wuri Sulistya Yekti; Reindy Rudagi; Jamurin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the shifting cultural values and traditions of the Tingkeban ceremony among the Javanese community in Nagari Padang Canduh, Kinali District, West Pasaman Regency. Such shifts are influenced by modernization, globalization, socio-economic changes, and intergenerational differences in perception. The research employed a descriptive qualitative method with data collected through in-depth interviews, participatory observation, and documentation. Informants included traditional birth attendants (dukun bayi), local community members, and the younger generation. The findings reveal that the Tingkeban ceremony, once rich in values of mutual cooperation, simplicity, spirituality, and respect, has undergone significant transformation. Traditional values have shifted toward individualism, materialism, and consumerism. Moreover, the younger generation’s understanding of the symbolic meanings of Tingkeban has declined, leading to the simplification of rituals. The main contributing factors to this shift include the influence of globalization, rapid technological development, and the community’s economic realities. Nevertheless, the younger generation holds great potential to revitalize and innovate the tradition to maintain its relevance. This study emphasizes that preserving the Tingkeban tradition is essential not only for safeguarding cultural heritage but also for strengthening the cultural identity and selfhood of the Javanese community in the face of modernization. Revitalization efforts through education, the role of cultural leaders, and the creativity of the younger generation are crucial to ensuring that the tradition endures. Keywords: Cultural Shift, Javanese Tradition, Tingkeban Ceremony, Modernization, Cultural Preservation.